Implementasi teknologi ALPAMAL dalam penyediaan air bersih untuk meningkatkan produktivitas usaha rumah tangga di Desa Tegalsari, Sidoarjo - Aurell Nathania Limetta; Stefanie Tjenderadjaja; Charleen Nicole Tan; Ocdio Howard Setiawan; Dhyah Harjanti; Surya Hermawan; Njo Anastasia (Nur Science Institute, 2026)
Tegalsari Village, Jabon Sub-district, Sidoarjo Regency, has limited access to clean water due to seawater intrusion, which impacts household health and micro-business productivity. This service programme aims to provide affordable access to clean water by implementing brackish-water purification technology using local materials (ALPAMAL), along with simple business management assistance. The method used was a participatory approach with data collection through a survey of 58 tool users, which was analysed using descriptive statistics. Results showed that 91.4% of respondents were satisfied with the water quality, 86.2% felt time efficiency, and most experienced a decrease in water costs. The utilisation of clean water also contributed to improved product quality, process hygiene, operational efficiency, and customer satisfaction of micro enterprises. These findings show that ALPAMAL technology is an effective, affordable, and sustainable water supply solution that improves the community’s quality of life and economic competitiveness.